Próba określenia systemów rolniczego użytkowania ziemi oraz poziomu ich intensywności w Polsce - Wysocki, Feliks (Digitalizacja i deponowanie archiwalnych zeszytów RPEiS sfinansowane przez MNiSW w ramach realizacji umowy nr 541/P-DUN/2016, 1990)
The article undertakes an attempt to determine the systems of agricultural exploitation of land for groups of provinces distinguished on the basis of similarity of structures of agricultural exploitation of land. The 1987 data on exploitation of farmland and the area of crops in particular provinces have been utilized. The research procedure consisted, in the first stage, in grouping the provinces according to the criterion of land exploitation structure and, in the second stage, according to the criterion of types of crops prevailing in a given structure. The findings allowed to ascribe names to different systems of land exploitation. The analysis resulted in distinguishing 19 groups of provinces similar from the point of view of land exploitation structure and 18 different types of systems. The above classifications were the basis for characterizing the systems and their intensity on the background of production conditions.
An attempt to determine the systems of agricultural exploitation of land and their intensity levels in Poland